Understanding the Inflationary Process in the GCC Region : The Case of Saudi Arabia and Kuwait - Alogeel, Hesham (IMF Working Papers; Working Paper, 2008)
This paper investigates the factors that affect inflation in the GCC region by examining the inflationary processes in Saudi Arabia and Kuwait. The paper utilizes a model that accounts for foreign factors affecting inflation, such as trading partners' inflation and exchange rate pass-through effect, as well as domestic influences. The analysis concludes that, in the long run, higher inflation in trading partners' countries is the main driving force for inflation in the two countries, with significant but lower contributions from the exchange rate pass-through effect and oil prices. Demand and money supply shocks affect inflation in the short run.